Studies on Adsorption of Manganese by Soils in the Presence of Electrolyte (Na2SO4) - Arora, Harsh; Bhardwaj, S.S.; Sharma, B.D. (Asian Journal of Chemistry, 2010)
Adsorption of manganese in the presence of Na2SO4 has been studied on nine soil samples from Punjab (S1 to S6) and Himachal Pradesh (S7 to S9) at 25° and 35°C. Adsorption of manganese increases with increase in concentration of adsorbate; adsorption isotherms being L-shaped. The adsorption of manganese decreases with increase in temperature. The. averaged values of partial molar free enegy change (ΔG) and apparent heats of adsorption ΔH have been calculated. The data conform to the Freundlich and the Langmuir equations.